Selected antecedents to approach status consumption of fashion brands among township youth consumers in the Sedibeng District - Madinga, Nkosivile Welcome (My University, 2016)
One important motivating force that influences a wide range of consumer behaviour is the desire to gain status or social prestige from the acquisition and consumption of goods. More often than not, individuals purchase expensive and luxury goods to display their social standing. In addition, individuals purchase status products to fulfil their material desires and reinforce their group identity. This is often a case with regards to youth consumers who often purchase expensive, luxury fashionable clothing brands to portray status and impress their peers. This behaviour seems to be trending among township consumers. The township market is a major contributor to the South African economy with an annual spending power of approximately R307-R308 billion. This study sought to investigate the influence of fashion clothing involvement, materialism and group identity on fashion brand status consumption amongst the youth. The research concentrates specifically on township youth consumers aged between 18 to 24 years, located in the Sedibeng district. This study made use of a non-probability convenience sample. A self-administered questionnaire was designed based on the scales used in previous studies. Five fieldworkers were selected and received training from the researcher on the purpose of the research as well as the critical elements of fieldwork. Once the training was completed, the questionnaires were distributed by fieldworkers. The questionnaire requested respondents to indicate on a five-point Likert scale the extent of their agreement or disagreement with items designed to measure their status consumption, fashion clothing involvement, materialism and group identity. In addition, the participants were requested to provide certain demographic data. For this study, a sample of 400 township youth individuals, residing within the Sedibeng district, was drawn. From this sample, only 345 questionnaires were usable leading to a response rate of 83 percent. The captured data were analysed using descriptive statistics and inferential statistics comprising of correlation and regression analysis. The findings indicate that fashion clothing involvement significantly and positively predicted status consumption of township youth consumers. Therefore, the results show that fashion-involved consumers are more likely to engage in status consumption. There was a direct relationship between materialism and status consumption. Group identity had a significant positive influence on status consumption. Owing to the high demand for status brands or products by township youth consumers, it is recommended that marketers should tap the market potential of this consumer segment while considering the influence of their reference groups. In addition, their advertisements should emphasise the brand or product’s ability to indicate status. Furthermore, marketers should make use of social media to effectively reach youth consumers. Insights gained from this study will help marketers to better understand township youth consumers, their engagement in status consumption, and their involvement in fashion clothing, which, in turn, should help them tailor their marketing efforts in such a way as to appeal to this segment in an appropriate manner.
M. Tech. (Marketing, Faculty of Management Sciences), Vaal University of Technology
Keywords: Customer behaviour; Social prestige; Luxury goods; Group identity; Clothing brands; Township market; Youth consumers; 338.47687; Clothing trade -- South Africa; Fashion merchandising -- South Africa.